Responsabilidade social empresarial no mercado de seguros brasileiro: influências culturais e implicações relacionais - Silva Filha, Therezinha Vollú da (2006)
The Brazilian insurance market is the ambience in which this research study takes place in search for a better understanding of how cultural characteristics are related with organizational signs, practices and expectations on social responsibility. The concepts of social responsibility as well as the concept of culture are presented and discussed from different points of view, in accordance with different authors and trough several methodological approaches, in order to establish a coherent theoretical basis for qualitative data analysis. The phenomenological attitude assumed by the researcher in especial dialogues situations during the field research phase added new possibilities of apprehension or emergence of each studied organization self orientation in terms of pre-occupation with social issues intimately related with their insurance activities in the market place. Final reflections show the complexity of the insurance cultural context in the studied Brazilian segment, in which cultural and subcultural national and organizational singularities appear. However leaving space for common values and coherent orientation toward the peculiar understanding of social responsibility as inherent to any insurance company activities, themselves. Last comments point out that future research studies may give additional contribution for the continuity of the discussions initiated in this dissertation, expecting that some changes in the organizational posture and practices may happen, especially those related with risk taking and broad processes of communication with clients and society as a whole.